2021
DOI: 10.1038/s41598-021-86224-z
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for influx of Atlantic water masses to the Labrador Sea during the Last Glacial Maximum

Abstract: The Last Glacial Maximum (LGM, 23–19,000 year BP) designates a period of extensive glacial extent and very cold conditions on the Northern Hemisphere. The strength of ocean circulation during this period has been highly debated. Based on investigations of two marine sediment cores from the Davis Strait (1033 m water depth) and the northern Labrador Sea (2381 m), we demonstrate a significant influx of Atlantic-sourced water at both subsurface and intermediate depths during the LGM. Although surface-water condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 92 publications
0
10
2
Order By: Relevance
“…In contrast to MIS 4, our records demonstrate a significant influx of Atlantic-sourced water at both subsurface and intermediate depths during the LGM (Seidenkrantz et al, 2019(Seidenkrantz et al, , 2021. Although surface-water conditions were cold and sea-ice loaded, the lower strata of the (proto) West Greenland Current carried a significant Atlantic (Irminger Sea-derived) Water signal, while at the deeper site the sea floor was swept by a water mass comparable with present Northeast Atlantic Deep Water (Seidenkrantz et al, 2021). The persistent influx of these Atlantic-sourced waters entrained by boundary currents off SW Greenland suggests an active Atlantic Meridional Overturning Circulation during the LGM.…”
Section: Labrador Sea Ocean Circulation and West Greenland Ice Sheet Extent During The Last Glaciationcontrasting
confidence: 62%
See 1 more Smart Citation
“…In contrast to MIS 4, our records demonstrate a significant influx of Atlantic-sourced water at both subsurface and intermediate depths during the LGM (Seidenkrantz et al, 2019(Seidenkrantz et al, , 2021. Although surface-water conditions were cold and sea-ice loaded, the lower strata of the (proto) West Greenland Current carried a significant Atlantic (Irminger Sea-derived) Water signal, while at the deeper site the sea floor was swept by a water mass comparable with present Northeast Atlantic Deep Water (Seidenkrantz et al, 2021). The persistent influx of these Atlantic-sourced waters entrained by boundary currents off SW Greenland suggests an active Atlantic Meridional Overturning Circulation during the LGM.…”
Section: Labrador Sea Ocean Circulation and West Greenland Ice Sheet Extent During The Last Glaciationcontrasting
confidence: 62%
“…Based on investigations of two marine sediment cores from the Davis Strait (1033 m water depth) and the northern Labrador Sea (2381 m), we see no evidence of warm-water flux to the West Greenland region during MIS 4, although the influx of Atlantic-sourced water at subsurface depth became extensive during MIS 3 (Seidenkrantz et al, 2019). In contrast to MIS 4, our records demonstrate a significant influx of Atlantic-sourced water at both subsurface and intermediate depths during the LGM (Seidenkrantz et al, 2019(Seidenkrantz et al, , 2021. Although surface-water conditions were cold and sea-ice loaded, the lower strata of the (proto) West Greenland Current carried a significant Atlantic (Irminger Sea-derived) Water signal, while at the deeper site the sea floor was swept by a water mass comparable with present Northeast Atlantic Deep Water (Seidenkrantz et al, 2021).…”
Section: Labrador Sea Ocean Circulation and West Greenland Ice Sheet Extent During The Last Glaciationcontrasting
confidence: 57%
“…Further afield, two sedimentary records from the northern Labrador Sea and Davis Strait, respectively, also suggest a stronger‐than‐present influx of warm Atlantic‐sourced water at both intermediate and deep‐water levels under near‐perennial sea ice cover (Seidenkrantz et al . 2019, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with reconstructions of Fagel et al (2002Fagel et al ( , 2004, who found no indication of DSOW presence prior to 8.6 ka based on radiogenic Nd and Pb isotope compositions of the clay fraction. However, a study by Seidenkrantz et al (2021) reported conditions comparable to the modern configuration in the deep Labrador Sea as early as 15 ka, potentially related to stronger overflow from the Greenland-Scotland Ridge. Different timings have been inferred for the initiation of the modern circulation in the Labrador Sea ranging from 14.3 ka based on Sm/Nd ratios and Nd isotope signatures of the carbonate free clay size fraction (Fagel et al, 1999) to ages not older than 10.3 ka (Innocent et al, 1997), 7.4 ka (Lochte, Repschläger, Seidenkrantz, et al, 2019) or even as late as 5.5 ka (Bilodeau et al, 1994).…”
mentioning
confidence: 97%